The semantics of interjections: An experimental study with natural semantic metalanguage. (20th July 2015) - GLADKOVA, ANNA; VANHATALO, ULLA; GODDARD, CLIFF
ABSTRACT: The paper reports the results of a pilot experimental study aimed at evaluating natural semantic metalanguage (NSM) explications of English interjections. It proposes a novel online survey technique to test NSM explications with language speakers. The survey tested recently developed semantic explications of selected English interjections as published in Goddard (2014a): wow, gosh, gee, yikes ("surprise" group) and yuck, ugh ("disgust" group). The results provide overall support for the proposed explications and indicate directions for their further development. It is interesting that respondents' preexisting knowledge of NSM and other background variables (age, gender, being a native speaker, or studying linguistics) were shown to have little influence on the test results.